Neutron detection with the Miniball germanium array - Andersson, Daniel (My University, 2015)
In experiment IS430 at Rex-Isolde, Cern, transfer reactions of neutron-rich beryllium isotopes on deuterated targets were studied with the segmented germanium detector array Miniball, detecting electromagnetic radiation, and the silicon-based T-Rex detector for charged particles. This thesis investigates signals in Miniball following inelastic scattering of neutrons on 72Ge, populating its first excited state which decays through ejecting a monoenergetic electron — a technique to detect neutrons in germanium detectors based on a proof-of-concept article. By correlating these neutron signals with additional event information, there is a possibility to draw a more complete picture of the reactions involved without the need to add additional detection equipment. Monitoring of these events could also have possible uses in online analysis of the neutron rate hitting the detectors, possibly degrading their function. This work investigates to which extent this process can be of help in the T-Rex and Miniball configuration at Isolde in particular, and for germanium detectors in general.
Keywords: Grundläggande vetenskaper; Fysik; Subatomär fysik; Kärnfysik; Lågenergifysik; Basic Sciences; Physical Sciences; Subatomic Physics; Nuclear physics; Low energy physics